The yield from routine chest X-rays in stage 3 breast cancer patients (2008)
Context: Cancer of the breast is a common malignancy in Nigeria women and various imaging examinations, including the chest radiograph are routinely requested in all patients with this disease. Objective: The objective of the study was to determine the positive yield from routines chest radiographs in Nigeria patients with locally advanced stage 3 breast cancers but who had no clinical symptoms or signs of plumonary or pleural metastatic disease. Methods: This descriptive retrospective study evealuated clinical records and chest radiographs of 61 female Nigerian patients with local stage 3 historically diagnosed breast cancers, who presented at the radiotherapy unit of the University College Hosiptal, Ibadan, over a 12 month period. All abnormalities on the chest radiographs were documented. Results: The ages of the study group ranged from 25 to 67 years with a mean of 47years. Fourty-seven (77%) of the patients had normal chest radiographs. Of the 14 abnormal radiographs, bilateral lung parenchymal metastases were seen in 4 cases one of whom also had bilateral pleural affusion. Other abnormal findings included hilar adenopathy, right lower lobe collapse, lymphagitis carcinomatosis and cardiomegaly. Conclusion: The authors conclude that a 23% detection rate from thses screening chest radiographs is high and should be recommended as over 70% of Nigerian patients with breat cancers present with advanced tumors.